PENERAPAN POMPA AIR TENAGA SURYA DAN PERALATAN PENCUCI TANGAN HIGIENES COVID-19 DI SMP DARUL ULUM AGUNG MALANG - Mizar, Muhammad Alfian; Marji, Marji; Hadi, Moch. Sholihul (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Universitas Negeri Malang, 2020)
Abstrak: Bidang pariwisata di Indonesia kini menjadi salah satu andalan pemeritah untuk menghasilkan devisa negara. Melimpahnya kekayaan alam yang dimiliki membuat setiap daerah di Jawa Timur mulai berkembang pesat dan menunjukan keunggulannya di tiap-tiap sektor. Terutama banyaknya potensi wisata alam yang ada di Kabupaten Malang Jawa Timur yang kini sudah mulai menampakkan eksistensinya hingga mampu menarik wisatawan nasional maupun internasional. Tujuan Pengabdian kepada Masyarakat ini adalah untuk mengembangkan teknologi Self Balancing Smart Scooter sebagai wahana wisata sehat untuk menambah daya tarik pengunjung witasawan.Â Teknologi Self Balancing Smart Scooter merupakan sebuah skuter roda dua bertenaga baterai. Kegiatan ini bertempat di Jl. Raya Selokerto, Godehan, Selorejo, Kec. Dau, Malang, Jawa Timur. Peserta berjumlah 25 orang dari mitra, masyarakat Desa Selorejo, dan Karangtaruna yang dilakukan selama tiga bulan. Hasil kegiatan meliputi: 1) perancangan desain, pembangunan, uji coba, hingga pembuatan sirkuit teknologi self balancing smart scooter, pelatihan perawatan teknologi self balancing smart scooter, serta evaluasi pasca kegiatan; 2) sirkuit teknologi Self Balancing Smart Scooter yang telah dibangun mampu meningkatkan pemasukan daerah; dan 3) sirkuit teknologi Self Balancing Smart Scooter yang telah dibangun mampu meningkatkan jumlah kunjungan wisatawan.Abstract: The tourism sector in Indonesia has now become one of the mainstays of the government to generate foreign exchange. The abundance of natural resources owned has made every region in East Java begin to develop rapidly and show its superiority in each sector. Especially the large number of natural tourism potentials in Malang Regency, East Java, which are now starting to show their existence so that they are able to attract national and international tourists. The purpose of this Community Service is to develop Self Balancing Smart Scooter technology as a vehicle for healthy tourism to increase the attractiveness of female visitors. Self Balancing Smart Scooter Technology is a battery powered two-wheeled scooter. This activity takes place at Jl. Raya Selokerto, Godehan, Selorejo, Kec. Dau, Malang, East Java. Participants totaled 25 people from partners, the people of Selorejo Village, and Karangtaruna which carried out for three months. The results of the activities include: 1) designing, building, testing, to manufacturing smart scooter self balancing technology circuits, training on maintenance of self balancing smart scooter technology, and post-activity evaluation; 2) Self Balancing Smart Scooter technology circuits that have been built are able to increase regional income; and 3) the Self Balancing Smart Scooter technology circuit that has been built is able to increase the number of tourist arrivals. 2) Self Balancing Smart Scooter technology circuits that have been built are able to increase regional income; and 3) the Self Balancing Smart Scooter technology circuit that has been built is able to increase the number of tourist arrivals. 2) Self Balancing Smart Scooter technology circuits that have been built are able to increase regional income; and 3) the Self Balancing Smart Scooter technology circuit that has been built is able to increase the number of tourist arrivals.